PERSEPSI SISWA TENTANG METODE MENGAJAR GURU DAN KEMANDIRIAN TERHADAP HASIL BELAJAR DALAM MATA PELAJARAN SENI BUDAYA KELAS XI SEMESTER 1 DI SMA NEGERI 13 - Rachmayanti , An'nisa (Program Studi Pendidikan Tari FBS UNJ, 2020)
This study aims to determine whether there is a relationship between students' perceptions of teacher teaching methods and learning independence on learning outcomes in the XI Semester 1 class of Arts and Culture at Tangerang N 13 High School. This research method uses quantitative types with correlational analysis techniques. The sampling technique used in this study was Simple Random Sampling, with a total sample of 38 students taken at random. Data collection techniques in the research instrument using a questionnaire and performance evaluation. The results of this study indicate 1) there is a significant positive relationship between students' perceptions of teaching methods of teachers towards learning outcomes in Cultural Arts subjects of 76.2%, with (r) 0.762, 2) there is a significant positive relationship between learning independence of learning outcomes in subjects Art and Culture by 76.3%, with (r) 0.763, 3) there is a significant positive relationship between students' perceptions of the teaching methods of teachers on learning independence in Art and Culture subjects by 75.0%, with (r) 0.750, 4) There is a significant positive relationship between students' perceptions about the teaching methods of teachers and learning independence of Art and Culture learning outcomes by 83.6%. The magnitude of the Correlation coefficient (r) of 0.836.